2018
DOI: 10.1016/j.neuropsychologia.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

The neural systems for perceptual updating

Abstract: In a constantly changing environment we must adapt to both abrupt and gradual changes to incoming information. Previously, we demonstrated that a distributed network (including the anterior insula and anterior cingulate cortex) was active when participants updated their initial representations (e.g., it's a cat) in a gradually morphing picture task (e.g., now it's a rabbit; Stöttinger et al., 2015). To shed light on whether these activations reflect the proactive decisions to update or perceptual uncertainty, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…When we presented healthy individuals with some of the gradually morphing picture sets used here in an fMRI experiment, we found that the anterior insula was active not only at the actual time point of reported object change but also about five seconds before—consistent with the involvement of the anterior insula in the exploration of alternative choices (Stöttinger et al 2015 ). We have recently replicated this finding (Stöttinger et al 2018 ).…”
Section: Discussionsupporting
confidence: 70%
“…When we presented healthy individuals with some of the gradually morphing picture sets used here in an fMRI experiment, we found that the anterior insula was active not only at the actual time point of reported object change but also about five seconds before—consistent with the involvement of the anterior insula in the exploration of alternative choices (Stöttinger et al 2015 ). We have recently replicated this finding (Stöttinger et al 2018 ).…”
Section: Discussionsupporting
confidence: 70%
“…Analogously, our age-related modulation in the ACC and seeming change in task-set importance could reflect distribution of task load. A possible mechanism involves perceptual updating, where insula and ACC activation appear when participants proactively update representations regardless of uncertainty (Stöttinger et al, 2018). In this scenario, older participants could be continuously updating their initial stimulus representations when there is a likelihood or chance for improving performance, as per our behavioral analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Second, people would exhibit surprise-driven learning when they were surprised. They were more likely to believe that the context had been changed, and information obtained before the surprise was no longer helpful in making predictions [17,33,58]. Therefore, people would discard their prior beliefs and emphasize newly arriving information, which led to participants being more sensitive to abrupt changes.…”
Section: Discussionmentioning
confidence: 99%